Experimental Study and Performance Enhancement of Surface Coating Techniques - Reddy, K. Samhitha; Reddy, V. Shreya; Sujitha, J.; Pydimalla, Madhuri (Techniques and Innovation in Engineering Research Vol. 6, 2022)
Surface coatings have changed over time to accommodate the changing demands of the processing sector. Powder coatings are desirable due to their adaptability, high performance and minimal environmental effect. This study aims to investigate the role of powder coatings in the evolution of conventional surface coating technology for practical applications in the field of metal coating, particularly with regard to office and home appliances. The primary objective of this paper is to provide a thorough analysis of the benefits and drawbacks of polymer powder coatings versus liquid-based coatings. The second objective was to compare polymer coatings to additive-filled powder coating. In this study, conventional substrates including copper, aluminum, galvanized iron, brass, cement plank, and wood block were utilized. For the priming coat, the materials were first dry scuffed and then immersed in a 3 in 1 chemical (a combination of zinc phosphate and magnesium phosphate). Coating the surfaces of the prepared substrates with spray-gunned liquid paint (on one side of the panel) and electrostatically sprayed powder paint (on the opposite side of the panel). The coated panels are subjected to a battery of standard (ISO) characterization tests, such as scratch hardness testing, flexibility testing, thickness testing, adhesiveness testing, impact resistance testing, etc., to further evaluate the coatings' efficacy. In comparison to liquid coatings, powder coatings demonstrated superior strength and durability (consistent with industry standards), and their qualitative results were promising (e.g., as the load progressively kept increasing i.e. 1000-2000 gms, mild scratches were noticeable on liquid coated substrates, whereas powder coated metal panels have shown a greater resistance to scratch damage). In addition, the characteristics and qualities of the powder-coated materials have been improved by the addition of a small amount of additive (such as graphene), which has withstood a scratch hardness test with a load of over 2500 gms. In this study, the benefits of powder coating technology have been validated, and the impact of fine powder flowability has been examined. Powder-coating thick steel components and even non-metallic substrates is a promising new direction that this study may open up. Recent advancements in powder coating technology with anticorrosion additives will also yield bonded metallic coatings with a distinctive, high-quality appearance.